(untitled) (E Conference Zone, 2022)
This article provides an overview of language learning strategies for second and foreign language teachers. To do so it outlines the background of LLS and LLS training, discusses a three step approach teachers may follow in using LLS in their classes, and summarises key reflections and questions for future research on this aspect of language learning education. It also lists helpful contacts and internet sites where readers may access up-to-date information on LLS teaching and research.